HADÂNAH PERSPEKTIF JAMA’AH TABLIGH - Hermanto, Agus (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2015)
Abstract : " Perspectives Hadânah Tablighis " Hadânah ismumayiz nurture children who have not (yet able to take care ofhimself ) . In the present era, has many Muslim pilgrims who focuses on propaganda sector and one of them is Tablighis. Khurûj fi sabilillah not only done by the husband, but the wife as the person in charge hadânah child's mother. Mastûrah (proselytizing efforts among women), one aim is to educate children in Islamic. Hadânah structurally is the husband'sresponsibility as the head of the household, but the task be given to his wife, Islam teaches that hadânah is the responsibility of the wife. Rights and obligations of parents towards children are trying to harness the power of which is owned as much as possible to provide suitable andappropriate education and discipline to teach their children. The rights of children that are jasadiyah, `aqliyah and rûhiyyah. In mastûrah is not allowed for children to participate in propaganda. Children entrusted to a grandmother or a close relative, and if you can not then be entrusted to another person who is able to care for children in accordance deal congregation. Cost still be given to people who take care, as the cost of radâ'ah. Law left the child relation to hadânah child is permissible, because his departure to think of religion, not to sin. Islam allows for parents to abandon children as long as his departure for religion, andthe child is entrusted to close relatives or to others by paying the cost of care.